Investigating the Impact of Problem-Based Learning on Academic Performance of Grade XII Students - Erni Yuniati (PGRI Provinsi Jawa Timur, 2022)
Traditional teaching methods have been found to be ineffective in promoting students’ critical thinking skills, real-world application, and engagement. To overcome these issues, this study aimed to examine the effectiveness of problem-based learning (PBL) as an alternative teaching method to enhance the academic performance of Grade XII students in MAN 1 Kota Madiun. Using a pre-experimental design, the research focused on a single class, specifically Class XII-IPS 2, with a sample of 32 students during the second semester of the academic year 2021/2022. The topic investigated was “How to Prepare Your Future”. The study assessed the impact of implementing PBL on students' academic performance by examining their engagement, critical thinking skills, and ability to apply their knowledge to real-life situations. The results indicated that the use of PBL significantly improved students' academic performance, as evidenced by increased engagement, enhanced critical thinking skills, and better application of knowledge. These findings highlight the potential of PBL as an effective teaching method to improve students' overall academic achievement. Therefore, it is recommended that educators and policymakers explore the integration of PBL into their curriculum to enhance students' critical thinking skills and better prepare them for future challenges.